SOIL pH VALUE ON AGRICULTURAL LAND USING COW STATE FERTILIZER - Selmi Yohana Stefanie; Novita Condro; Nias F. Pusop (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2022)
Fertilizer is an organic fertilizer derived from animal manure in the form of solid, liquid, and food scraps mixed together. One example of this type of manure is manure from cow dung. The purpose of this study was to identify soil pH in three different locations, namely Komba, Koya and Youtefa, Jayapura Regency. This research was carried out in the life sciences lab of the Faculty of Agriculture, Forestry and Marine Affairs, University of Ottow Geissler Papua.The method in this research is the experimental method. Soil samples were taken from different locations, namely Koya, Komba, and Youtefa. The parameters observed were soil pH, the data were processed descriptively. The results showed that there were differences in the quality index of the soil pH at each location, which tended to be acidic, namely in the Komba area, the soil pH was 6.62, Koya the soil pH was 6.22, and in Youtefa the soil pH 7.18